Pesantren and Politics: Moral and Social Values in Santri Character Formation - Mhd Wildan Arifin Batubara; Abu Sahrin (International Journal of Multidisciplinary Research of Higher Education, 2026)
The internalization of moral and social values in pesantren does not always occur uniformly, as it is influenced by students’ family backgrounds, parenting styles, and technological developments. This study aims to analyze the process of internalizing theological and social moral values, their practical application in students’ daily lives, the influencing factors, and the role of Pondok Pesantren Mawaridussalam in shaping santri character. A qualitative method with a phenomenological approach was employed. Data were collected through participatory observation, interviews, and documentation, involving 20 informants consisting of pesantren leaders, teachers, student care administrators, and santri representatives. Data analysis was conducted through reduction, presentation, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that theological and social moral values are internalized through teacher role modeling, leadership training, educational guidance, worship habituation, deliberation, layered supervision, and the implementation of rewards and sanctions. The core values instilled include sincerity, muraqabah (self-vigilance), trust in God, responsibility, justice, equality, honesty, accountability, and social concern. The success of this internalization is supported by 24-hour boarding life, structured evaluation, and collaboration with parents, while differences in family background and technology use remain significant challenges. These findings affirm that pesantren functions not only as a moral education institution but also as a training ground for social leadership among santri.